Modeling the low-carbon behaviors' development paths of freight enterprises based on a survey in Zhejiang, China. (July 2022) - Wu, Chengcheng; Xiao, Le; Hu, Zheng; Zhou, Yijun
Highlights: Extreme value theory was used to model the low-carbon's development path. Enterprises in low-GDP regions are more likely to adopt new low-carbon behaviors. Enterprises in high-GDP regions may stop exploring new low-carbon behaviors. Abstract: Improving freight enterprises' low-carbon behaviors is a significant measure in reducing carbon emissions and thus promoting cities' sustainable development. This paper aimed at modeling how various freight enterprises' low-carbon behaviors vary with their development. A province-wide investigation of 980 freight enterprises was conducted, then the K-means clustering method and Extreme value theory (EVT) mode were adopted to identify the low-carbon development paths of freight enterprises. The results show that: a) freight enterprises with short-distance freight transportation in low-GDP areas have the lowest low-carbon degree (LCD), but they have the highest probability to adopt low-carbon behaviors when LCD>30.37; b) freight enterprises in high-GDP regions have the lowest willingness to adopt low-carbon behaviors when the development degree is higher than 201.5. The findings help to understand the low-carbon development path of freight enterprises at different stages, and it's useful for government to accurately adopt low-carbon development measures in road freight transportation.